Multivessel Coronary Artery Vasospasm-Induced Takotsubo Cardiomyopathy - Vishal I. Patel; Serap Sobnosky (Case Reports in Cardiology, 2022)
Takotsubo cardiomyopathy is associated with a constellation of cardiac findings including reversible left ventricular dysfunction and an acute triggering stressor. Epicardial coronary vasospasm is a rarely reported etiology for takotsubo cardiomyopathy, and its pathophysiologic mechanisms still remain incompletely understood. We present the case of a 54-year-old female with chest pain and ST-elevation myocardial infarction who was found to have takotsubo cardiomyopathy due to diffuse multivessel coronary artery vasospasm in the absence of obstructive coronary artery disease. To our knowledge, this is the first angiographically confirmed case of this rare phenomenon to be reported, as most literature involves focal, segmental, or single coronary artery involvement. Moreover, we review current literature and develop a discussion on the targeted treatment of vasospastic disease as part of the multimodal approach to the management of takotsubo syndrome.